Fibromyalgia Syndrome In Geriatric Population - Berrin Leblebici; Nur Turhan; Mehmet Adam; Nuri Çetin; Selda Bağış (Archives of Rheumatology, 2009)
Objective: The aim of this study was to investigate the frequency and the associated features of fibromyalgia syndrome (FMS) which plays a significant role in the chronic pain syndromes, and also to compare the pain variables in solitary osteoarthritic (OA) patients versus osteoarthritis plus FMS patients, in a group of elderly patients. Material and Methods: One hundred and twenty four patients who aged over 65 and who were consecutively admitted to the Physical Medica and Rehabilitation outpatient clinics were enrolled this study. Sixty-five patients who had no painful diseases other than OA and/or FMS were investigated by means of their clinical and radiological features and essential laboratory tests. The diagnosis of FMS was made according to the criteria of American College of Rheumatology. All FMS patients were also evaluated by Fibromyalgia Impact Questionnaire. Pain parameters included visual analog scale (VAS), the number of degenerative joints, antiinflammatory and analgesic drug intake, and the number of tender points (NTP). Results: The mean age of all patients (97 female, 27 male) was 70.56±5.05 years, the mean age of menapause was 46.04±7.08 years. Forty seven out of 124 (37.9%) were having FMS. Fourtytwo of this FMS patients also had OA. Twenty three patients had only OA. There were statistically significant higher values in VAS scores and incidence of psychiatric problems in OA+FMS patient group (n=42, mean age=69.19±4.23 years), when they were compared to the OA patient group (n=23, mean age=70.6±4.32 years) (p<0.001, p:0.03). Conclusion: In the elderly, FMS is a very common problem, which mostly accompanies degenerative joint diseases and give rise to exagerated painful conditions (Turk J Rheumatol 2009; 24: 6-9)